Prospects of India-Bangladesh economic cooperation: Implications for South Asian regional cooperation - Prabir De; Biswa N. Bhattacharyay (Asian Development Bank Institute (ADBI), 2007)
In recent years, South Asia has received growing attention as a region that is integrating successfully into the global economy. To maximize the benefits in terms of faster growth and poverty reduction, the region will need to strengthen regional and bilateral cooperation in several areas. In this context, closer bilateral cooperation and integration between major South Asian countries, such as between India and Bangladesh, will strengthen the South Asian Association for Regional Cooperation (SAARC) and help ensure the effectiveness and efficiency of their activities. Cultural, trade, and economic exchanges between the two countries are long standing. India and Bangladesh boast of a total population of more than 1 billion, and their rapid domestic economic development and good cooperation have demonstrated broad prospects for further cooperation. A remarkable growth in two-way trade between India and Bangladesh has resulted in robust growth of the economies in the region. India has become Bangladesh's largest trading partner in South Asia. Compared with their strength, much potential exists for developing trade and economic relations between the two countries. This paper discusses various opportunities and associated prospects and problems in strengthening the India-Bangladesh economic cooperation and integration agenda in the context of SAARC.
Keywords: F10; F15; R40; 330; Internationale Wirtschaftsbeziehungen; Indien; Bangladesch; Südasien